Interaction of Multiwalled Carbon Nanotube Produces Structural Alteration of DNA (2016)
Multiwalled carbon nanotube (MWCNT) has been found to produce structural changes in Calf Thymus-DNA (CT-DNA). The interaction or binding of the multi-walled carbon nanotubes (MWCNT) was investigated in order to discover if it brings about any significant changes of the DNA double helix using CD spectra of the CT-DNA at two concentration levels of MWCNT representing an increasing MWCNT/DNA molar ratio. In addition, spectrophotometric titrations between MWCNT and CT-DNA were carried out in order to utilize spectral changes as a means of detecting specific binding modes of either intercalation or degradation of DNA. Interactions of MWCNT induced significant changes in the CD spectra of the B-form of natural DNA. The intensities of the positive CD band at 280 nm decreased significantly. This decrease was found to be concentration-dependent. Following spectrophotometric titrations; specific subtle conformational changes were observed with a molar ratio combination of 2:1 between MWCNT and CT-DNA and these were characterized by a formation constant of the order of 103 M-1 and a negative Gibbs free energy suggesting that MWCNT avidly binds to DNA. Thermodynamic considerations revealed that electrostatic interactions between the DNA base pairs and the MWCNT are taking place accounting for the negative free energy change, positive enthalpy change with a small entropy change. The results obtained in the study of the binding interactions of MWCNT with DNA confirm that a cytogenetic effect of MWCNT with DNA is a possibility in vivo.